(untitled) (GAIMS Journal of Medical Sciences, 2023)
Background: Around 70% of the Indian population are from rural areas and around 28 percent of the population live in below poverty line; the out of pocket expenditure on health is quite a burden to the household. A report found that the coverage falls short of the desirable coverage of 25% according to the National Health Policy. Studies regarding government health schemes in the rural population are scarce. Hence, this study was conducted with objectives to assess the perception about national health schemes and to determine association between perceptions with various socio-demographic variables among patients attending Rural Health Training Centre (RHTC) of a medical college. Methods: A cross sectional study was carried out among 107 patients attending OPD at RHTC. Data was collected with convenience sampling technique using pretested, semi-structured questionnaire. The responses were entered and statistically analysed by using SPSS v.20. Chi square test was applied to know the association between demographic variables and perception. Results: About 60 (56.07%) participants perceived the health schemes to be beneficial to common man. While, 45 (42.05%) participants disagreed that they had adequate knowledge of scheme. Perception of agreement regarding its benefits was proportionately higher in males-46 (60.52%), in ≤50,000 income- 47 (69.11%) and with card availability 55 (80.88%). Perception of agreement with respect to ‘Protection from unexpected cost’ by various schemes is proportionately higher in males- 32 (58.18%) and with card availability- 34 (61.81%). Perception of agreement regarding its willingness to utilize schemes was proportionately higher in ≤30 years of age- 39 (55.71%). Conclusions: Majority of the participants agree that these schemes are beneficial and provide quality and affordable treatment and protects from unexpected costs. Majority of participants are willing to utilise these schemes. Therefore, it is the need of the hour to increase awareness of schemes among people.